Strengthening pancasila leadership character of village governments through dynamic portfolio based learning - Sriharjo, Sadono; Dasim Budimansyah; Encep Syarief Nordin; Yadi Ruyadi; Muhammad Yaumi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
The crisis of exemplary Pancasila leadership within Village Governments, who act as central figures in the economic, socio-cultural, and governance transformation process for comprehensive, gradual, and sustainable village development, forms the background of this research. This study aims to develop a theory on the characteristics of Pancasila leadership for Village Governments, with a specific focus on the Village Sustainable Development Goals (Village SDGs). Utilizing a Mixed Method Grounded Theory approach, data was collected through surveys, observations, and interviews with representatives from Village Governments across 39 3T (Remote, Border, Outermost) villages and 335 non-3T villages in 20 regencies. The findings reveal a strong understanding and clear perception of Pancasila values as the state ideology, which is reflected in various aspects of village governance such as policy-making, networking, and development activities. The application of Pancasila in the operational aspects of village governance, in relation to the Village SDGs, demonstrates an understanding of how Pancasila and the Village SDGs work synergistically. This highlights key factors that strengthen leadership character within village government, including effective leadership application and the recognition of the relationship between Pancasila and the Village SDGs. Theoretically, this research contributes to the development of a contextual Indonesian leadership theory. In terms of policy, the findings recommend the integration of Pancasila values into village development planning and performance appraisal systems. Practically, the study yields a dynamic portfolio model as a tool for village officials to reflect on and document their leadership performance